The given D.E is a lin ear 1st order differential equation:
"(x^2-x-2)\\frac{dy}{dx}+3xy =( x^2-4x+4)"
Now this can be rewritten as
"\\frac{dy}{dx}+\\frac{3x}{(x^2-x-2)}*y=\\frac{(x^2-4x+4)}{(x^2-x-2)}"
"or, \\frac{dy}{dx}+\\frac{3x}{(x+1)(x-2)}*y=\\frac{(x-2)^2}{(x+1)(x-2)}\\\\or, \\frac{dy}{dx}+\\frac{3x}{(x+1)(x-2)}*y=\\frac{(x-2)}{(x+1)}"
Calculating INTEGRATING FACTOR (I.F)
"I.F= e^{\\int {\\frac{3x}{(x+1)(x-2)}}dx}"
"Now \\int {\\frac{3x}{(x+1)(x-2)}}dx = \\int \\{\\frac{1}{x+1}+\\frac{2}{x-2}\\}dx"
"=\\int \\frac{1}{x+1}dx + 2\\int \\frac{1}{x+2}dx"
"= log|x+1|+2log|x+2|"
"= log\\{(x+1)(x-2)^2\\}"
"\\therefore I.F = e^{log\\{(x+1)(x-2)^2\\}}=(x+1)(x-2)^2"
The solution to the given D.E is
"\\therefore y* (x+1)(x-2)^2= \\int \\{(x+1)(x-2)^2\\frac{(x-2)}{(x+1)}\\}dx +C\\\\or, y* (x+1)(x-2)^2= \\int (x-2)^3dx+C"
"or,y* (x+1)(x-2)^2= \\frac{(x-2)^4}{4}+C"
The required solution is
"y* (x+1)(x-2)^2= \\frac{(x-2)^4}{4}+C"
ANSWER
Comments
Leave a comment